Isolation of Human PBMCs - Santosh Panda; Balachandran Ravindran (Bio-Protocol, 2013)
Peripheral blood mononuclear cells (PBMCs) are chiefly lymphocytes and monocytes. PBMCs are separated from the whole blood by a density gradient centrifugation method using Ficoll Histopaque.